Observed and Expected Questions in the Social Book for the Second Intermediate Grade according to Critical Thinking Skills - Mustafa, Manar Youssif; Mathqoor, Bushra Hassan (Al-Adab Journal, 2021)
This study aims at investigating the availability of critical thinking skills included in the observational and expected questions in the book of socials for the second Intermediate grade. The descriptive approach was used for the content analysis. And to achieve the objectives of the study, a tool for critical thinking skills was prepared which included six main skills: interpretation, analysis, evaluation, conclusion, Explanation, self-regulation, as the questions of the end of the chapters were analyzed especially in the second grade book in the light of the critical thinking skills and after the completion of the analysis and to confirm the validity of the tool based on the validity of experts and specialists, and verified the reliability of the analysis through the agreement with an external analyst and with the researcher herself over time. The researcher relied on statistical means, including the Cooper equation and Chi Square Test to identify the differences between the variables of the tool (observed repetition and expected repetition) and frequencies and percentages, and the social book for the second grade with the obtained percentages in the questions observed: (15.13%, 24.04%, 15.13%, 13.06%, 13.06%, 19.58%) respectively. The Intermediate Second grade social book received the percentages in the expected questions (20%, 25%, 5%, 20%, 25%, 5%), and we note through the values as any calculated critical thinking skills (40.67) at the level (0.05) and the degree of freedom (5) and the value of scheduling (11.07). This indicates the decrease of compatibility between the observed and expected questions which means the absence of questions that measure the higher processes of critical thinking among the students. Consequently, the study came up with some conclusions, recommendations and proposals.